Histiocytoid Sweet's syndrome presenting with annular erythematous plaques - Renata Marcarini; Raquel Nardelli de Araujo; Monisa Martins Nóbrega; Karina Bittencourt Medeiros; Alexandre Carlos Gripp; Juan Manuel Piñeiro Maceira (Sociedade Brasileira de Dermatologia, 2016)
Abstract Histiocytoid Sweet's Syndrome is a rare inflammatory disease described in 2005 as a variant of the classical Sweet's Syndrome (SS). Histopathologically, the dermal inflammatory infiltrate is composed mainly of mononuclear cells that have a histiocytic appearance and represent immature myeloid cells. We describe a case of Histiocytoid Sweet's Syndrome in an 18-year-old man. Although this patient had clinical manifestations compatible with SS, the cutaneous lesions consisted of erythematous annular plaques, which are not typical for this entity and have not been described in histiocytic form so far. The histiocytic subtype was confirmed by histopathological analysis that showed positivity for myeloperoxidase in multiple cells with histiocytic appearance.